Transforming businesses with bitcoin mining and blockchain applications - Rajput, Dharmendra Singh, 1985-; Thakur, Ramjeevan Singh, 1974-; Basha, Syed, 1986- (Premier reference source., 2020)
"This book examines the use of bitcoin mining and blockchain applications in business"--